Pemurnian dan Pembaharuan Islam - Srijudin Srijudin; Salma Afra Khoirunnisak; Annisa Dzulvina Jamila (Universitas Muhammadiyah Klaten, 2025)
This article aims to focus this research on the purification and renewal of Muhammadiyah, specifically in the field of muamalah in the Islamic world. The type of research used in this study is qualitative research, which is a method useful for obtaining scientific knowledge from a particular document or other literature presented by previous and current scientists through literature study. Islamic renewal has been underway for a long time. Over the past few centuries, we have seen the role of various Muslim figures in developing and packaging Islam in various forms. At its core, it is a unified effort to spread and preach Islam throughout the world. The emergence of the renewal movement was inspired by the need for change in various aspects of life. In the religious aspect itself, it is hoped that the Islamic renewal movement can help people understand Islam again in accordance with the Qur'an and Sunnah. Avoiding all innovations, superstitions, myths, and superstitions that are deeply rooted in traditionalist communities. These communities are greatly influenced by local traditional culture and customs. Additionally, it is hoped that this movement can combat and correct anything that contradicts the teachings of Islamic sharia. The results of the study indicate that problems in the field of muamalah can be resolved in accordance with the Qur'an, Surah an-Nisa (4): 29, which prohibits reducing the weight of scales and can be resolved by being fair and honest. And Surah al-Baqarah (2): 282, which contains a command to practice kindness and honesty, can resolve issues related to debt and credit